Educação e classe : uma análise sobre as percepções ambientais dos brasileiros - Mendonça, Cássio Gonçalves (2022)
The quest for a sustainable society goes through the recognition of the environmental issues and the reorganization of pro-environmental habits and behaviors. Climate change affects people of all social ranks and educational levels. In front of this scenario, this study has the objective of analyzing the environmental perceptions of Brazilians. For this purpose, the data collected by Instituto de Tecnologia & Sociedade do Rio in its research “climate change in the perception of Brazilians” is analyzed through the creation of four profiles, consisting of combinations of educational levels and class ranks. We use cross table analysis with the chi-square Pearson test to understand how the different profiles behave in relation to environmental worries, climate perception and pro-environmental behaviors. As a result, the study found a positive relationship between environmental perceptions and higher levels of education and income, Brazilians tend to recognize environmental issues.